Assessment of Knowledge and Use of Hiv Post Exposure Prophylaxis and Healthcare Workers’ Risk to Occupational Exposure in New Juabeng Municipality - Babanawo, G.F. (University of Ghana, 2016)
Background: Human immunodeficiency virus since its discovery has grown to become a public health menace. Healthcare workers are at risk of acquiring HIV infection as a result of managing HIV infected patients. Post exposure prophylaxis (PEP), a confirmed method, decreases the possibility of sero-conversion to HIV after occupational exposure. This study aimed at assessing the level of knowledge on post exposure prophylaxis, determining the level of risk to occupational injuries and to determine the patronage of PEP among healthcare workers in the New Juabeng Municipality. Method: A cross-sectional study conducted among 185 healthcare workers comprising of doctors, nurses, midwives and laboratory technicians between the period of May and July 2016. Quantitative data was collected using self-administered structured questionnaires and analyzed with stata software version 13.0. Results: Majority of respondents (96.8%) considered themselves to be at risk of occupational exposure. About 83.2% had occupational exposure within the last 12 months. The commonest sources of injuries were from needle stick (48.6%) and splashes of bodily fluids (66.5%). More than two thirds (87.7 %) of respondents were using a personal protective equipment (PPE) at the time of exposure. Of the exposed, 51.9% were eligible to take PEP, but only 33.8% reported to have received the PEP. A substantial proportion of respondents (97.3%) heard of the existence of the PEP concept and majority (90.8%) established that PEP is effective in preventing HIV. About 89.2% knew the right first aid to perform and 65.4% knew who to contact first after exposure. Approximately 93% were familiar with time of commencement but only 38.9% knew the duration of PEP. Conclusion: knowledge and patronage of PEP is low among HCWs despite high prevalence of occupational injuries. There is the need for training to increase the level of knowledge, improve patronage and reduce the incidence of occupational injuries among HCWs in the New Juabeng Municipality. Key words: HIV, post exposure prophylaxis, knowledge, healthcare workers, New Juabeng Municipality.
Thesis(MPH)-University of Ghana, 2016
Keywords: Hiv Post Exposure Prophylaxis; Healthcare Workers’ Risk; New Juabeng Municipality